DuMont's Künstler-Lexikon von 1945 bis zur Gegenwart. - Thomas, Karin; de Vries, Gerd (Köln : Dumont Buchverlag Köln, 1977)
Abrahams, Ivor ; Acconci, Vito ; Acht, René Charles ; Ackermann, Peter ; Adami, Valerio ; Aeppli, Eva ; Aeschbacher, Hans ; Afro ; Agam, Yaacov ; Albers, Josef ; Albert, Hermann ; Albrecht, Joachim ; Alcopley ; Alechinsky, Pierre ; Alfano, Carlo ; Alt, Otmar ; Altenbourg, Gerhard ; Alvermann, Hans Peter ; Alviani, Getulio ; Anatol ; Anceschi, Giovanni ; Andersen, Eric ; Anderson, Laurie ; Andre, Carl ; de Andrea, John ; Annesley, David ; Anonima-Gruppe ; Anselmo, Giovanni ; Antes, Horst ; Antonakos, Stephen ; Anuskiewicz, Richard ; Appel, Karel ; Apple, Billy ; Arakawa, Shusaku ; Arman ; Armando ; Armitage, Kenneth ; Arnim, Bettina von ; Arroyo, Eduardo ; Art & Language ; Artschwager, Richard ; Asher, Michael ; Askevold, David ; Asmus, Dieter ; Atkinson, Terry ; Atlan, Jean-Michel ; Attersee, Christian Ludwig ; Aubertin, Bernard ; Avramidis, Joannis ; AY-O ; Aycock, Alice ; Bacon, Francis ; Badura, Michael ; Baer, J. ; Baertling, Olle ; Baier, Jean ; Bailey, William ; Bainbridge, David ; Baldessari, John ; Baldwin, Michael ; Bandau, Joachim ; Barker, Clive ; Barry, Robert ; Bartolini, Luciano ; Baruchello, Gianfranco ; Basaldella, Mirko ; Baschlakow, Alexej Iljitsch ; Baselitz, Georg ; Baumgarten, Bodo ; Baumgarten, Lothar ; Baumgartl, Monika ; Bay, Didier ; Bayrle, Thomas ; Bazaine, Jean ; Baziotes, William ; Beal, Jack ; Becher, Bernd & Hilla ; Bechtle, Robert ; Beckley, Bill ; Bell, Larry ; Bengston, Billy Al ; Benkert, Ernst ; Benton, Fletcher ; Bergander, Rudolf ; Berner, Bernd ; Berrocal, Miguel ; Bertholin, Jean-Marie ; Beuys, Joseph ; Biasi, Alberto ; Biel, Michael von ; Bill, Max ; Bioulès, Vincent ; Bissier, Julius ; Bissière, Roger ; Bladen, Ronald ; Blake, Peter ; Blume, Bernhard Johannes ; Bluth, Manfred ; Bochner, Mel ; De Boer, Saskia ; etc.
Bibliog. p. 76-82
Stromingen van de eerste helft van de 20ste eeuw p. 14-75
Duits
boek